Effect of immortal time bias on the association between atrial fibrillation ablation and incident stroke: a meta-analysis. (25th November 2020) - Samuel, M; Khairy, P
Abstract: Background/Introduction: In the era of big data and large observational studies, identification and prevention of immortal time bias (ITB) is essential to attain unbiased effect estimates. Immortal time refers to a period of follow-up in a cohort when the outcome cannot occur. Typically, it results when the exposure is initiated after the start of follow-up. The misclassification of person-time results in a systematic overestimation of the treatment effect. ITB is a common methodological issue in epidemiology studies. We sought to assess the presence and magnitude of bias due to ITB in observational studies evaluating the effectiveness of catheter ablation (CA) for atrial fibrillation. Purpose: To compare the association between CA and stroke in 1) observational studies that controlled for ITB, 2) observational studies that did not address ITB, and 3) randomized controlled trials (RCT). Methods: The PUBMED database was screened from inception to January 15, 2020 for publications with the following string of search terms: ("ablation" or "catheter ablation" or "pulmonary vein isolation") and "atrial fibrillation" and ("stroke" or "thromboembolism"). Observational studies and RCTs comparing CA to medical therapy were eligible. Studies were excluded if: 1) evaluation of the association was limited to a subgroup of AF patients, 2) cryoablation was performed, 3) strokes were not reported, and 4) HRs or 95% CI were not presented. Information on study characteristics, HRs, and the potential for ITB was extracted. Subsequently, articles were classified based on the type of study and whether ITB was addressed. For each group of articles, HRs were logarithmically transformed and pooled using the random effects model. Results: A total of 10 observational studies and 1 randomized controlled trial were included in the present analysis. Of the 10 observational studies, only 2 studies were designed to prevent ITB. The pooled HR for observational studies without ITB prevention showed a statistically significant reduction in risk of stroke (HR 0.66 (95% CI 0.58–0.74); I2=27.3%) in CA patients compared to non-CA patients. However, pooling the two observational studies that prevented ITB indicated no difference in the incidence of stroke [HR 0.75 (95% CI 0.49–1.02); I2=4.5%] among patients with and without CA, a finding similar to CABANA trial [HR 0.42 (95% CI 0.11–1.21)]. Conclusion: It is important to evaluate the effectiveness of procedures and medications using observational data to determine if the results from RCTs translate to the real-world. However, careful consideration needs to be taken in the design phase to avoid ITB and produce effect estimates that more accurately represent the true association between treatment and outcomes. Examples of design methods to prevent ITB include the use of a time-varying covariate or matching on pre-treatment exposure time. Funding Acknowledgement: Type of funding source: None